If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 8 = -3y + -8 Reorder the terms: 8 + -4y = -3y + -8 Reorder the terms: 8 + -4y = -8 + -3y Solving 8 + -4y = -8 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 8 + -4y + 3y = -8 + -3y + 3y Combine like terms: -4y + 3y = -1y 8 + -1y = -8 + -3y + 3y Combine like terms: -3y + 3y = 0 8 + -1y = -8 + 0 8 + -1y = -8 Add '-8' to each side of the equation. 8 + -8 + -1y = -8 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = -8 + -8 -1y = -8 + -8 Combine like terms: -8 + -8 = -16 -1y = -16 Divide each side by '-1'. y = 16 Simplifying y = 16
| a-9-5a=-25 | | 90+7x-10+2x+10=180 | | m-11/2=-5/4 | | 7=4z-(2z+1) | | 6=-3(x) | | 10x+9=109 | | 9*9=81 | | 4x-6(3-x)=13 | | 1.5x+.5=-1.0 | | 14*2=x | | 2-1=1 | | -5x-13=7 | | 2+4x=55 | | 3x+2=2(x+6) | | 2r-6(-10+r)=-7 | | 72-4x=5x+21 | | 7-2s+5s+8=13s+25-5s | | 5*2*(-4)+3*6= | | 20-x=-0.68*(20+x) | | x(x+8)-8(x+8)= | | 32-4=3x-26 | | 6x^2-60x+126= | | -3y+5y-4=-7+4y | | 6x^3+29x^2+27x-20=0 | | x^2+(k-1)x+4=0 | | -3h-1=11 | | 4x^2-x+11=0 | | 2x^4-4x^3+2x^2+2x= | | 2x^2-x+1=x^2-4x-1 | | 2+d=4d-2 | | 119-2x=25x+17 | | -3(x+4)=27 |